SOME STRATEGIES IN TEACHING LISTENING FOR EYL - Novianty, Melisa; Lastari, Putri Maisaroh (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2023)
Listening English is a challenging for the teachers of English. The teachers have to study hard, focus to listen, think and describe what the speakers talk about, practice listen and listen again, learn how to improve their listening skill, and transfer their knowledge for the students. In this case, the writer gives information for some strategies in teaching listening for EYL (English Young Learners). In addition, the teacher can use the strategies to teach the students. These strategies can inspire teachers to teach and students to learn. They actually can improve their listening skill if they want to study, practice more and more in their daily life. Besides, EYL means to focus in Elementary school students. The teachers of English teach listening for EYL by giving some strategies in learning process. If the EYL hard to listen, the teacher have to motivate, give spirit to students, and never give up to learn. It is because listening skill is very important not only for today but also forever in life. Hopefully, all of these strategies will be useful for EYL, teachers of English, another researchers, and others. Mendengarkan Bahasa Inggris merupakan sebuah tantangan bagi para guru Bahasa Inggris. Guru harus belajar giat, fokus mendengarkan, memikirkan dan mendeskripsikan apa yang dibicarakan pembicara, berlatih mendengarkan dan mendengarkan lagi, belajar bagaimana meningkatkan keterampilan mendengarkan, dan mentransfer pengetahuannya kepada siswa. Dalam hal ini, Penlulis memberikan informasi tentang beberapa strategi dalam pengajaran mendengarkan untuk EYL (English Young Learners). Selain itu, guru dapat menggunakan strategi untuk mengajar siswa. Strategi-strategi ini dapat menginspirasi guru untuk mengajar dan siswa untuk belajar. Mereka sebenarnya dapat meningkatkan keterampilan mendengarkannya jika mereka mau belajar, berlatih lebih banyak, dan lebih banyak lagi dalam kehidupan sehari-hari. Selain itu, EYL artinya fokus pada siswa Sekolah Dasar. Guru bahasa Inggris mengajarkan mendengarkan EYL dengan memberikan strategi dalam proses pembelajaran. Jika EYL sulit untuk mendengarkan, guru harus memotivasi, memberi semangat kepada siswa, dan pantang menyerah untuk belajar. Hal ini karena keterampilan mendengarkan sangat penting tidak hanya untuk saat ini tetapi juga selamanya dalam kehidupan. Semoga semua strategi ini bermanfaat bagi EYL, guru bahasa Inggris, peneliti lain, dan lain-lain.